Identification of biomarkers in patients with rheumatoid arthritis responsive to DMARDs but with progressive bone erosion - Marasco, Emiliano; Fabbriciani, Gianluigi; Rotunno, Laura; Longhi, Matteo; De Luca, Paola; de Girolamo, Laura; Colombini, Alessandra (Frontiers in Immunology, 2023)
Introduction: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that may cause joint destruction and disability. The pharmacological treatment of RA aims at obtaining disease remission by effectively ceasing joint inflammation and arresting progressive bone erosions. Some patients present bone lesions accrual even after controlling joint inflammation with current therapies. The aim of our work is to analyze lymphocyte subsets and levels of circulating cytokines in patients with RA with progressive bone erosions.Methods: we enrolled 20 patients with a diagnosis of RA and 12 healthy donors (HD). RA patients were divided in patients with bone erosions (RA-BE+) and without bone erosions (RA-BE-). Lymphocytes subsets in peripheral blood were evaluated by flow cytometry. Circulating cytokines levels were evaluated by protein array.Results: distribution of lymphocyte subsets was not able to separate HD from AR patients and RA-BE+ and RA-BE-in cluster analysis. We observed a significant expansion of CXCR5 -PD1 + T peripheral helper cells (Tph cells) and a reduction in both total memory B cells and switched memory B cells in RA patients compared to HD. We observed an expansion in the frequency of total B cells in RA-BE+ patients compared to RA-BE-patients. Unsupervised hierarchical clustering analysis of 39 cytokines resulted in a fairly good separation of HD from RA patients but not of RA-BE+ patients from RA-BE-patients. RA-BE+ patients showed significantly higher levels of IL-11 and IL-17A than RA-BE-patients.we show that patients with progressive erosive disease are characterized by abnormalities in B cells and in cytokines with a proven role in bone reabsorption. Understanding the role played by B cells and the cytokine IL-11 and IL-17A in progressive erosive disease, can help identifying novel biomarkers of erosive disease and designing treatment approaches aimed at halting joint damage in RA.